Η "Πανοπλία δογματική" του Ευθυμίου Ζιγαβηνού στον κώδικα Parisinus gr. 1310 - NIKOY Δημήτριος (Byzantina Symmeikta, 2024)
The texts inscribed on ff. 146v-152v of codex Parisinus gr. 1310 (15th c.) are wrongly regarded as coming from different works of John Chrysostom. This article shows that they are parts of Euthymios Zigabenos’ Panoplia Dogmatica, which, once identified, were traced to their source; the text delivered by this codex was then compared both to the edition and to the older codices containing the work, and the differences are noted